Metabolic features of myeloma cells in the context of bone microenvironment: Implication for the pathophysiology and clinic of myeloma bone disease - Raimondi, Vincenzo; Toscani, Denise; Marchica, Valentina; Burroughs-Garcia, Jessica; Storti, Paola; Giuliani, Nicola (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is a hematological malignancy characterized by the accumulation of malignant plasma cells (PCs) into the bone marrow (BM) leading to alteration of the microenvironment including a severe impairment of bone remodeling. In turn, BM cells exert a critical role in the regulation of the survival of MM cells. Growing evidence indicates that MM cells have several metabolic features such as enhanced glycolysis and lactate production through the upregulation of glucose transporters and enzymes. More recently, it has been reported that MM cells are highly glutamine addicted. Interestingly, these metabolic changes of MM cells may affect BM microenvironment cells by altering the differentiation process of osteoblasts from mesenchymal stromal cells. The identification of glutamine metabolism alterations in MM cells and bone microenvironment may provide a rationale to design new therapeutic approaches and diagnostic tools. Currently, The Positron Emission Tomography (PET) with 18F-fluorodeoxyglucose (FDG) is the diagnostic gold standard to detect active MM bone disease based on the high glycolytic activity of MM cells. However, new tracers are actively under investigation because a portion of MM patients remain negative at skeletal level by 18F-FDG leading to the development of alternative PET tracers with promising results to detect MM cells in the bone. In this paper, we will review the current knowledge on the metabolic alterations of MM cells in the contest of their bone microenvironment. Additionally, we will discuss the identification of possible new druggable targets, the use of novel targets for PET imaging in the detection of bone lesions, and in the staging and treatment response of MM patients have been discussed.